Selaginella austro-orientalis (Selaginellaceae), a new species from Southeast China - Wei, Hong-Jin; Chen, Bin; Fang, Shao-Li; Zhou, Xin-Mao (Phytotaxa, 2023)
Selaginella subg. Heterostachys, especially S. sect. Heterostachys and S. sect. Tetragonostachyae, represents the most taxonomically difficult subgenus of Selaginella in China. Here, Selaginella austro-orientalis, a new species in S. sect. Heterostachys from Southeast China is described and illustrated based on morphological and phylogenetic studies. Morphologically, the new species is most similar to S. heterostachys, but differs by its broadly ovate ventral leaves with slightly cuspidate apex and strobili with megasporangia only at ventral side.